2022
DOI: 10.1177/23779608221094541
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance in the Context of HIV: A Concept Analysis

Abstract: Due to the differing definitions of the concept of sleep disturbance among people living with human immunodeficiency virus (HIV), reviewers in this area have not reached any firm conclusions. The study aimed to clarify and provide a stronger foundation for the definition of sleep disturbance in the context of HIV to enhance the concept’s development. Following Beth Rodgers’ concept analysis guidelines, two leading databases were searched, and 73 articles were used for this concept analysis. The attributes, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The current study attempted to investigate a theoretically plausible link by identifying predictor variables of sleep in PLWH, including social rhythms, depression, social support, and coping styles. Based on the social zeitgeber theory and existing evidence, we propose the following four hypotheses ( 1 ): Social rhythms directly predict sleep quality ( 2 ), social support and coping styles (active coping, passive coping) directly predict social rhythms ( 3 ), social support and coping styles (active coping, passive coping) indirectly predict sleep quality through social rhythms, and ( 4 ) there was a bidirectional predictive association between sleep and depression. The hypothetical model is presented in Figure 1 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study attempted to investigate a theoretically plausible link by identifying predictor variables of sleep in PLWH, including social rhythms, depression, social support, and coping styles. Based on the social zeitgeber theory and existing evidence, we propose the following four hypotheses ( 1 ): Social rhythms directly predict sleep quality ( 2 ), social support and coping styles (active coping, passive coping) directly predict social rhythms ( 3 ), social support and coping styles (active coping, passive coping) indirectly predict sleep quality through social rhythms, and ( 4 ) there was a bidirectional predictive association between sleep and depression. The hypothetical model is presented in Figure 1 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A meta-analysis showed that the prevalence of selfreported sleep disturbances in PLWH was 58% (1). The sleep disturbances reported by PLWH mainly included reduced total sleep time, difficulty falling asleep, difficulty maintaining sleep, sleep reinitiation disorder, daytime dysfunction, excessive dreaming, and irritability (2)(3)(4). Sleep disturbances can contribute to a series of adverse consequences for PLWH, such as greater depressive symptoms (5), poorer health-related quality of life (6), increased risk of incident cardiovascular disease (7), lower HIV medication adherence, and self-reported increased HIV symptom severity (8).…”
Section: Introductionmentioning
confidence: 99%